The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1445-2197.2008.04683.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards Painless Colonoscopy: A Randomized Controlled Trial on Carbon Dioxide‐insufflating Colonoscopy

Abstract: Insufflation with CO2 during colonoscopy results in less pain during and after the examination. Because of better tolerance, colonoscopy with CO2 insufflation might gain wide acceptance in the community to be used as a screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 15 publications
3
59
0
Order By: Relevance
“…As for the time of cecal intubation and sedation doses used, there was no difference between using CO 2 or air, in agreement with other previously published studies (9,12,14) and in disagreement with others that have reported a lesser cecal intubation time (8,18) or lower doses of midazolam in patients who underwent endoscopic submucosal dissection (22). We also found no differences between groups in terms of time spent in the recovery room after the colonoscopy, which was probably due to the high workload of the nurse in charge of this room.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As for the time of cecal intubation and sedation doses used, there was no difference between using CO 2 or air, in agreement with other previously published studies (9,12,14) and in disagreement with others that have reported a lesser cecal intubation time (8,18) or lower doses of midazolam in patients who underwent endoscopic submucosal dissection (22). We also found no differences between groups in terms of time spent in the recovery room after the colonoscopy, which was probably due to the high workload of the nurse in charge of this room.…”
Section: Discussionsupporting
confidence: 92%
“…Another benefit we observed in our study, although not quantified, was the realization that the patient who had undergone a colonoscopy with CO 2 felt less shame when experiencing less flatulence, which made them have an immediate perception of comfort and tolerance to exploration. Both the decrease in pain experienced and the feeling of shame is likely to have a positive impact on the increasing acceptance of colonoscopy, although this aspect could not be confirmed by studies that tried unsuccessfully to find differences in the percentages of patients who said they were willing to accept a colonoscopy of screening of colorectal cancer in the future, few minutes after undergoing a colonoscopy with CO 2 or air (12,14). Certainty of safety is a fundamental aspect when recommending the use of CO 2 insufflation during a colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of RCT in unsedated or sedated patients summarized in a review of methods of reducing discomfort during colonoscopy 1 and in more recent reports [8][9][10] showed that CO 2 instead of air insufflations decreases pain scores and increases the proportion of patients with no pain after colonoscopy. The mechanism is based on 'rapid' absorption of CO 2 from the lumen, decreasing distention and associated pain.…”
Section: Biographymentioning
confidence: 99%
“…It has been also suggested using carbon dioxide, which is rapidly absorbed and excreted through lungs, as an insufflating gas for colonoscopy to reduce these symptoms [54,55]. Also water immersion technique instead of air insufflation has been proposed to reduce these minor events especially in cases of minimal sedation [56] (Leung 2010).…”
Section: Abdominal Pain and Other Minor Gi Symptomsmentioning
confidence: 99%